THE ROLES OF LANGUAGE AND COMMUNICATION IN RELATION TO ORGANIZATIONAL CULTURE AT PT. ASTRA INTERNATIONAL MEDAN-BINJAI NORTH SUMATERA - Sari, Indah (Linguistik : Jurnal Bahasa dan Sastra, 2024)
Language refers to a tool for communication and it has some functions such as transferring information, conveying ideas, opinions, and thoughts, acquiring knowledge, motivating along with appreciating people. This study used descriptive qualitative design by administering the open questionnaires to twelve employees at PT. Astra International Medan-Binjai North Sumatera. The results of this study are language and communication have a great role in relation to organizational culture and it is very important in the company. Moreover, the reasons are to make the work be successful and run well, to reach company goals, to avoid mistakes and misunderstandings, to motivate and appreciate the people in the organization, and to create the comfortable environment of work in the company.